2005
DOI: 10.1007/bf03167054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral administration of benzylamine on glucose tolerance and lipid metabolism in rats

Abstract: Repeated administration of benzylamine plus vanadate have been reported to exhibit anti-hyperglycemic effects in different models of diabetic rats. Likewise oral treatment with Moringa oleifera extracts which contain the alkaloïd moringine, identical to benzylamine, has also been shown to prevent hyperglycemia in alloxan-induced diabetic rats. With these observations we tested whether prolonged oral administration of benzylamine could interact with glucose and/or lipid metabolism. Seven week old male Wistar ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
3
13
0
1
Order By: Relevance
“…Our results perfectly confirm the findings of a preliminary experiment performed with Wistar rats showing that oral administration of benzylamine (1870 μmol/kg/day) did not decrease of food and water consumption (5). Moreover, they reproduced our observation of the benefits of orally given benzylamine on glucose handling to diabetic monse model by VHFD feeding.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results perfectly confirm the findings of a preliminary experiment performed with Wistar rats showing that oral administration of benzylamine (1870 μmol/kg/day) did not decrease of food and water consumption (5). Moreover, they reproduced our observation of the benefits of orally given benzylamine on glucose handling to diabetic monse model by VHFD feeding.…”
Section: Discussionsupporting
confidence: 81%
“…However, benzylamine has been reported to exert diverse insulin-like effects by itself, without need for vanadate, such as stimulation of glucose transport and inhibition of lipolysis in human fat cells (13), adipogenesis in murine preadipocytes (17), and improvement of glucose tolerance in conscious rabbits and in obese mice (12). Moreover, we have recently reported that chronic oral administration of benzylamine to normoglycemic non obese rats was able to reduce their hyperglycemic response to a glucose load (5). The aim of the study was therefore to test whether oral benzylamine administration was able to improve glucose tolerance in a diabetic model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic elevation of blood glucose, mostly often with no symptoms present to alert the individual to the presence of diabetes, will eventually lead to tissue damage and consequently serious disease in many organ systems such as the kidneys, liver and vascular system (6,7,9,11). Also hyperglycemia lead to the dysfunction of the reproductive system in men and rats (2,19).…”
mentioning
confidence: 99%
“…30,31 Moringa oleifera significantly decreased the incidence of hyperglycemia in 2 animal studies. 30,31 In a study of fed and fasting Wistar rats, Bour et al 30 found that benzylamine, an active ingredient in Moringa oleifera, significantly improved glucose tolerance and decreased free fatty acids. 30 In another study of Wistar rats, Ndong et al 31 found that Moringa oleifera improved glucose tolerance and decreased glucose uptake in response to slowed gastric emptying.…”
Section: Endocrine Systemmentioning
confidence: 97%